Submental Myodermal Flap in Buccal Reconstruction after Extended Combined Resection - N. V. Kovalenko; A. Yu. Nenarokomov; A. I. Ivanov; S. Ye. Tolstopyatov; V. V. Zhavoronkova; A. G. Chukhnin; D. L. Speransky; T. F. Deviatchenko (Креативная хирургия и онкология, 2021)
Background. Oral mucosal cancer is the most prevalent squamous cell cancer of head and neck, with 6,723 cases registered in Russia, including 94 per Volgograd Region, in 2018. A high tumour advancement and complex topography of the surgical area result in extensive soft-tissue defects and impaired swallowing, chewing and speech.Aim. Efficacy assessment of submental myodermal flap application in buccal reconstruction after extended combined oncological resections.Materials and methods. Submental myodermal flap was used as a buccal reconstruction technique in 112 patients aged 42 to 75 years during 2015–2020. Surgery for primary tumour was performed in 88 cases, and in 24 — for recurrence after radiotherapy or surgical excision.Results and discussion. A six-year experience of the submental myodermal flap usage in reconstructive surgery allowed evidently wider indications for extensive oral resection combined with extended, also bilateral, lymphadenectomy. Clinical records on the technique application in primary and recurrent cancer are presented.Conclusion. The submental myodermal flap technique in combination with extended or extended combined surgery for oral mucosal cancer notably increases the tumour resectability at this location and improves function restore in patients. The method widens indications for higher-volume operative aid, considerably reduces postoperative complications and holds a promise to enable more radical surgery. This plastic surgery technique is aesthetic and effectively repairs speech and digestive functions, bringing improvement to the patients’ quality of life and social adaptation.